Determination of critical levels of residual oxygen to minimize discoloration of sliced packaged Norwegian salami under light display. (July 2017) - Sørheim, Oddvin; Måge, Ingrid; Larsen, Hanne
Abstract: Discoloration of sliced packaged salami is contributing to rejection of the product, food waste and economical loss. A combination of residual O2 in the headspace of packages and light is causing photooxidation and deterioration of colour. The aim of this study was to establish maximum tolerable concentrations of residual O2 in packages of salami slices with 100% N2 under light display at 4 and 20 °C. Salami sausages had variable inherent O2 consumption rate. Storage of salami in 1% O2 in darkness did not induce discoloration. The upper limits for O2 for avoiding discoloration under light were variable in the range 0.1–1.0%, depending on temperature and type of salami. Display at 20 °C increased the rate of O2 depletion compared to 4 °C. To minimize discoloration, sliced and packaged salami should be stored in darkness at approximately 20 °C until the level of residual O2 is reduced below a critical limit. Highlights: Discoloration of salami occurs by a combination of residual O2 and light. Maximum O2 headspace concentrations to avoid discoloration in light were 0.1–1.0%. Depletion of residual O2 from headspace was faster at 20 than 4 °C. Keep sliced packaged salami in darkness until residual O2 has passed a critical level.